Status of Stock Market Concentration and Turnover at Nepal Stock Exchange - Rajesh Gurung (Pravaha, 2022)
This paper examines the status of stock market concentration and turnover in Nepal Stock Exchange (NEPSE) during the period from Mid-July 2003-04 to Mid-July 2019-20. Despite the NEPSE’s high concentration and low degree of liquidity, the research reveals that stock market concentration and turnover are gradually improving, with the banking sector playing a key role in market concentration. It also finds a negative association between market concentration and stock turnover, meaning that a decrease in stock concentration is accompanied by an increase in turnover (or liquidity) across the study period. This has important policy implications, particularly in terms of reducing the market concentration and improving liquidity. Encouraging family-owned business to go public and attracting international capital flows so as to reduce investment risk and increase confidence of market participants in the capital market of Nepal.